PROBLEMATIKA CALON INDEPENDEN DALAM PEMILIHAN UMUM KEPALA DAERAH - Eka Martini AR, Ni Putu; R., Ibrahim (Kertha Semaya : Journal Ilmu Hukum, 2013)
In this paper with titled "The Problems of Independent Candidates in the GeneralElection" issues that discuss are about what are the legal basis for the setting ofindependent candidates and what problems that will be faced by independent candidates inthe election. The method used is the method of normative legal by research with statuteapproach and the conceptual approach, while legal materials collection techniques usingliterature study which was the materials collected analyzed qualitatively. The results at themoment is that the participation of independent candidates in the election have beenguaranteed by laws, but in reality an independent candidate faces several problems in anelection. The conclusion that Indonesia's Constitution in 1945 and the Law No. 12 Year2008 on the Second Amendment to Law No. 32 Year 2004 on Regional Governancen arethe legal basis for independent candidates, while the problems that faced as a consequenceof independent candidates are : 1. The independent cadidates do not have the politicalmachinery to access voter, 2. bear the political cost by themselves, and if elected he shouldbe able to adjust the balance of power by members legislature as a 3. result of not havingpolitical support in the legislature.
Keywords: Independent candidates, Election of Regional Heads